Exploring Mental Health Prevalence Among Multiethnic High School Adolescents in West Kalimantan - Hendrik Hendrik; Yenni Rizal; Hendra Sulistiawan; Melina Lestari; Ely Trisnowati; Uray Herlina; Hema Fitria; Dada Suhaida (AL-ISHLAH: Jurnal Pendidikan, 2025)
Mental health among adolescents is a growing concern, particularly in culturally diverse regions. This study investigates the mental health status of multiethnic adolescents at State Senior High School 1 Sungai Kakap, West Kalimantan, Indonesia, focusing on six major ethnic groups: Malay, Dayak, Chinese, Bugis, Madurese, and Javanese. A quantitative, descriptive research design was employed. Data were collected through a mental health assessment and analyzed using percentage calculations. Each participant’s score was categorized, and the proportion of individuals in each category was computed by dividing the frequency (ni) by the total number of participants (n), then multiplied by 100. Findings indicate that, overall, the mental health of multiethnic adolescents falls within the "high" category. However, some variations emerged across ethnic groups, with certain students—particularly at State Senior High School 1 Sungai Kakap—showing lower mental health scores. Among the four dimensions assessed—physical, psychological, moral-religious, and social—the psychological aspect scored the lowest, suggesting it is the most vulnerable area. The lower scores in psychological well-being highlight a pressing need for targeted interventions. Cultural diversity may contribute to unique stressors that affect adolescents' psychological health more than other domains. This study underscores the importance of enhancing adolescent mental health, particularly the psychological dimension, in multiethnic contexts. School-based guidance and counseling programs, alongside strong family and community support, are recommended to foster better mental health outcomes.